Innovating Services in Science and Technology Parks - NARASIMHALU, Arcot Desai (Institutional Knowledge at Singapore Management University, 2013)
Science and Technology Parks are in the business of providing services to their tenants, a mix of large companies, Small and Medium Enterprises and startups. The service needs of each of these types of companies will be different. The quality of services can be improved by understanding the needs of the tenants both, prior to building the Science and Technology Parks as well as on an ongoing basis. This paper introduces the CUGAR model for Science and Technology Parks as well as Service Innovation Design framework. It then proceeds to discuss how the Service Innovation framework could be applied to Science and Technology Parks. It uses an example to show how services can be prioritized and selected for implementation within the available budget.